Cu0.8Mg1.2Si2O6 : a copper-bearing silicate with the low-clinopyroxene structure. (2nd January 2018) - Ding, Lei; Darie, Céline; Colin, Claire V.; Bordet, Pierre
Abstract: The Cu0.8 Mg1.2 Si2 O6 pyroxene has been synthesized using a soft chemistry method. Its crystal structure was determined from powder X-ray diffraction data. Cu0.8 Mg1.2 Si2 O6 crystallizes with the lowclinopyroxene monoclinic structure (space group P21 /c). The role of the Jahn-Teller-distorted Cu2+ cation on the stability of this strongly distorted structure is investigated. Cu 2+ shows a strong preference for the M2 site, attributed to a better adaptation of its JT-distorted coordination polyhedron to this already distorted and more flexible site. Comparison with previously reported compounds indicates that increasing the Cu content enhances the M2 site distortion, eventually leading to symmetry lowering from orthorhombic Pbca to monoclinic P21 /c. These observations bring new insight into the mechanisms of formation and chemical composition of pyroxene minerals in the presence of JT cations.